Enhanced electrical energy storage performance of Pb-free A-site La3+-doped 0.85Na0.5Bi0.5TiO3-0.15CaTiO3 ceramics. Issue 18 (15th December 2020) - Yu, Linjiang; Dong, Jia; Tang, Mingyang; Liu, Yi; Wu, Fei; Yan, Yan; Liu, Gang; Song, Chunlin
Abstract: A conventional preparation method of electroceramics was used to synthesise Pb-free 0.85Na0.5 Bi0.5 TiO3 -0.15CaTiO3 - x La (NBT-CT- x La) ceramics. La 3+ doping effectively refined the grains and enhanced the dielectric breakdown strength (BDS) of the ceramics; this result was confirmed by numerical simulations, which revealed that grain refinement significantly contributed to the enhancement of the BDS. The energy storage density consequently improved when an appropriate amount of La 3+ was added to the NBT-CT ceramics. In particular, the NBT-CT-0.75La ceramic displayed a maximum energy storage density of 2.15 J/cm 3 and a high BDS of 210 kV/cm. This ceramic also possessed relatively excellent temperature and frequency stabilities (30–150 °C, 0.2–200 Hz). Moreover, the ceramics exhibited exceptional charge–discharge performances, with an outstanding power density of 43.87 MW/cm 3, which is nearly twice of that of other NBT-based ceramics. On the basis of the findings, the NBT-CT-0.75La ceramic can be considered to be a promising candidate material for the pulsed power application.